Vapor-phase polymerized poly(3,4-ethylenedioxythiophene) on a nickel nanowire array film : aqueous symmetrical pseudocapacitors with superior performance - Xie, Qisen (2018)
Three-dimensional (3D) nanometal scaffolds have gained considerable attention recently because of their promising application in high-performance supercapacitors compared with plain metal foils. Here, a highly oriented nickel (Ni) nanowire array (NNA) film was prepared via a simple magnetic-field-driven aqueous solution deposition process and then used as the electrode scaffold for the vapor-phase polymerization of 3,4-ethylenedioxythiophene (EDOT). Benefiting from the unique 3D open porous structure of the NNA that provided a highly conductive and oriented backbone for facile electron transfer and fast ion diffusion, the as-obtained poly(3,4-ethylenedioxythiophene) (PEDOT) exhibited an ultra-long cycle life (95.7% retention of specific capacitance after 20 000 charge/discharge cycles at 5 A/g) and superior capacitive performance. Furthermore, two electrodes were fabricated into an aqueous symmetric supercapacitor, which delivered a high energy density (30.38 Wh/kg at 529.49 W/kg) and superior long-term cycle ability (13.8% loss of capacity after 20 000 cycles). Based on these results, the vapor-phase polymerization of EDOT on metal nanowire array current collectors has great potential for use in supercapacitors with enhanced performance.